Role of HALP score in predicting short term outcomes after surgery in esophago-gastric cancers - Kharel, Ashish; Thakur, Binay; Khatiwada, Sagar; Tiwari, Manoj; Bhattarai, Shachee; Adhikari, Mahesh Mani; Sapkota, Sandeep; Thapa, Shrijana (Nepalese Journal of Cancer, 2025)
Background: Esophago-gastric cancers are common cancers with poor prognosis. Radical surgery offers the best hope for long term survival but is associated with increased short-term morbidity and mortality. There is a need for a simple scoring system that helps in estimating the short-term prognosis of the patient after undergoing surgery for these cancers. Hemoglobin, Albumin, Lymphocytes, Platelets (HALP) score is such a scoring system that has recently been developed. The aim of this study was to evaluate the role of HALP score in predicting short term outcomes after surgery in esophago- gastric cancers. Methods: We conducted a prospective study of all patients with esophago-gastric cancers undergoing curative intent surgery in the surgical oncology department. The optimal HALP cut-off point was evaluated using Receiver operating characteristics (ROC) analysis and the cohort was divided into Low and High HALP groups, which were then further analyzed. Results: The mean age was 61.52 ± 9.07 years. Of these 17 (54.8%) were male and 14 (45.2%) were female. Squamous cell carcinoma was the more common histology. The optimal cut-off value of HALP was 38.0 with a sensitivity of 86.7% and specificity of 87.5%. Low HALP was significantly associated with Anastomotic leak, SSI, overall mortality and prolonged hospital stay. Conclusion: HALP score can be a good prognostic indicator for patients with esophago-gastric cancers undergoing curative resection.